(untitled) (Лучшие интеллектуальные исследования, 2025)
ABSTRACT. The article analyzes the role of substantivates — words reinterpreted from other parts of speech as nouns — in various speech styles. The features of their use in artistic, scientific, colloquial and official-business styles, as well as the influence of substantivates on the expressiveness and functionality of the text are considered. Examples from fiction, scientific works and everyday speech are given, and recommendations for their stylistic use are given. The material is addressed to philologists, teachers and students studying the stylistics of the Russian language.